Diffusion Dynamics of Energy-Efficient Renovations Causalities and Policy Recommendations - Müller, Matthias otto.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Accelerating the diffusion of energy-efficient renovations is a key policy lever in order to reduce the environmental impact of buildings. This book provides a broad, systemic perspective on the causes of the diffusion of energy-efficient renovations in Switzerland and policy recommendations for accelerating the diffusion process. Specifically, the book provides a description of the societal problem situation within which the diffusion process takes place and an analysis of the actors involved. It provides a detailed explanation of the causes of the diffusion process that synthesizes insights from the engineering, economics, marketing, sociology, communication studies and political science literature. It employs the System Dynamics methodology to simulate the diffusion process and analyze policy levers. The book proposes two regulations and a sketch of a business model as particularly promising public policy interventions. It concludes with an outline of a generic theory of the diffusion of sustainable technologies. .
Introduction -- Research Design and Methods -- Climate Change, Energy Use Patterns and the Stock of Buildings -- A Small Model for the Analysis of the Transformation of the Stock of Buildings -- Actors in the Societal Problem Situation -- A Feedback Perspective on the Diffusion of Energy-Efficient -- A Rich Model of the Diffusion Dynamics of Energy-Efficient -- Transformation of the Societal Problem Situation -- Discussion and Conclusions -- Materials Published in the Electronic Supplements -- Model Testing -- A Fictitious Example of the Immobility Business Model -- Glossary.
Keywords: Energy efficiency; Buildings—Design and construction; Building; Construction; Engineering, Architectural; Sustainable development; Energy Efficiency; Building Construction and Design; Sustainable Development